Effect of metoclopramide in guinea-pig ileum longitudinal muscle: evidence against dopamine-mediation. Issue 1 (January 1982) - Zar, M A; Ebong, O; Bateman, D N
Abstract : The investigation examines the hypothesis that metoclopramide-induced potentiation of gastrointestinal motility is mediated through dopamine receptors. In vitro studies on the longitudinal muscle of the guinea-pig ileum were performed. Metoclopramide, in concentrations comparable with those seen in plasma after therapeutic doses in man, selectively potentiated the cholinergic response Dopamine (1-100 microM) inhibited cholinergic transmission by inhibiting neuronal acetylcholine release. The inhibitory action of dopamine was antagonised by phentolamine, and alpha-adrenoceptor antagonist, but not by the dopamine receptor antagonists metoclopramide or primozide. Bromocriptine inhibited cholinergic responses by a postsynaptic mechanism which was not antagonised by metoclopramide, primozide, or phentolamine. The results are consistent with the view that metoclopramide-induced potentiation of gastrointestinal motility does not involve local dopamine receptors.